Technology and analysis of ancient gemstones : proceedings of the European workshop held at Ravello, European University Centre for Cultural Heritage, November 13-16, 1987 = Technologie et analyse des gemmes anciennes : actes de l’Atelier Européen tenu à Ravello, Centre Universitaire Européen pour les Biens Culturels, 13-16 Novembre 1987 (Strasbourg)
458 s.